Cyclooxygenase-2: A Role in Cancer Stem Cell Survival and Repopulation of Cancer Cells during Therapy - Lisa Y. Pang; Emma A. Hurst; David J. Argyle (Hindawi Limited, 2016)
Cyclooxygenase-2 (COX-2) is an inducible form of the enzyme that catalyses the synthesis of prostanoids, including prostaglandin E2 (PGE2), a major mediator of inflammation and angiogenesis. COX-2 is overexpressed in cancer cells and is associated with progressive tumour growth, as well as resistance of cancer cells to conventional chemotherapy and radiotherapy. These therapies are often delivered in multiple doses, which are spaced out to allow the recovery of normal tissues between treatments. However, surviving cancer cells also proliferate during treatment intervals, leading to repopulation of the tumour and limiting the effectiveness of the treatment. Tumour cell repopulation is a major cause of treatment failure. The central dogma is that conventional chemotherapy and radiotherapy selects resistant cancer cells that are able to reinitiate tumour growth. However, there is compelling evidence of an active proliferative response, driven by increased COX-2 expression and downstream PGE2 release, which contribute to the repopulation of tumours and poor patient outcome. In this review, we will examine the evidence for a role of COX-2 in cancer stem cell biology and as a mediator of tumour repopulation that can be molecularly targeted to overcome resistance to therapy.